Rogue access point detection mechanism considering sequence number of beacon frame for wireless local area networks - Ketkhaw, Apisak; Thipchaksurat, Sakchai (My University, 2017)
Rogue Access Point (RAP) is one of the serious problem concerned with the security issues. The attacker usually inserts the RAP by setting the information such as Service set identifier (SSID), MAC Address and beacon frame size same as those of the legitimate AP. In this paper, we propose the mechanism for RAP Detection by considering sequence number of beacon frame in wireless local area networks (WLAN). Our proposed mechanism considers sequence number of beacon frame by introducing checking detection window technique for detecting the RAP. We show the effectiveness of mechanism by conducting an experiment. The results show the our proposed mechanism is able to detect RAP accurately.
Keywords: Access Point; Beacon frame; Rogue Access point; WLAN